Peroperative Nerve Preservation During Open Hernia Repair (Bangladesh Journal of Anatomy, 2010)
Background: Peroperative identification and subsequent division or preservation of the inguinal nerves during open hernia repair may influence the incidence of chronic postoperative pain. Methods: A systematic literature review was performed to identify studies investigating the influence of different types of nerve management. Results: Based on three randomized studies the pooled mean percentage of patients with chronic pain after identification and division of the ilioinguinal nerve was similar to that after identification and preservation of the ilioinguinal nerve. Two cohort studies suggested that the incidence of chronic pain was significantly lower after identification of all inguinal nerves compared with no identification of any nerve. Another cohort study reported a significant difference in the incidence of chronic pain in favour of identification and facultative pragmatic division of the genital branch of the genitofemoral nerve compared with no identification at all. Conclusion: The nerves should be identified during open hernia repair. Division of and preservation of the ilioinguinal nerve show similar results. Incidence of postoperative chronic pain may be decreased by preservation of inguinal nerves in open hernia repair. DOI: 10.3329/bja.v8i1.6108 Bangladesh Journal of Anatomy January 2010, Vol. 8 No. 1 pp. 39-42